Mast cells in atherosclerosis - Bot, Ilze; Biessen, Erik A. L. (Thrombosis and Haemostasis, 2011)
The mast cell, a potent inflammatory cell type, is widely distributed over several tissues, but particularly prominent at the interface exposed to the environment to act in the first line of defense against pathogens. Upon activation mast cells release granules, which contain a large panel of mediators, including neutral proteases (e.g. chymase and tryptase), cathepsins, heparin, histamine and a variety of cytokines and growth factors. While mast cells have been demonstrated to be critically involved in a number of Th2 dominated diseases such as asthma and allergy, recent investigations have now also implicated mast cells in the pathogenesis of atherosclerosis and acute cardiovascular syndromes. In this review, we will discuss the contribution of mast cells to the initiation and progression of atherosclerosis and gauge the therapeutic opportunities of mast cell targeted intervention in acute cardiovascular syndromes.
Keywords: Atherosclerosis; mast cell; plaque stability; proteases; cytokines; acute cardiovascular syndromes